Diagnostic Wax and Mock-up Technic Use and Property as a Diagnostic Method for the Performing Sector Anterior Composite Resins (International Journal of Medical and Surgical Sciences, 2015)
Today dental surgeries for cosmetic alterations have been increasing, considering that the anterior teeth are mainly seen when a person speaks or smiles, it makes it clear that these are essential actors in the aesthetics of a patient. However we must also worry about preserving and / or return of guides disclusion order to achieve a mutually protected occlusion. With technological advances that have occurred in this adhesion can be achieved by perfectly composed with a minimally invasive technique and lower cost resins. It is presented to view a patient who has just completed his orthodontic treatment, and which the specialist told her to be multiple cavities in molars, but to perform the initial review we have a serious cosmetic problem in the upper front teeth, is He offered to treat that patient problem through a diagnostic wax technique, Mock-up and subsequently performing through direct resin restorations. The purpose of presenting this clinical case illustrates a technique of modified Mock-up is useful both as a diagnostic and for different steps in the same restorative treatment tool.